Phenology of Atlantic Rain Forest Trees: A Comparative Study - Morellato, L. Patnicia C.; Talora, Daniela C.; Takahasi, Adrians; Bencke, Cinara C.; Romera, Eliane C.; Zipparro, Valescka B. (Biotropica, 2000)
This paper describes the phenology of leaf, flower, and fruit phenology in the Atlantic rain forests of southeastern Brazil. For 17 months, we observed the phenological patterns of trees from two Atlantic forest types at four sites: premontane forest (Sites I and IV; the "typical" Atlantic rain forest) and coastal plain forest (Sites II and III). All sites experience a nonseasonal, tropical wet climate, characterized by an annual rainfall usually > 2000 mm and lacking a dry season. We tested for the occurrence (or absence) of seasonal phenological patterns within each site and compared the patterns detected among the four different forest sites using circular statistics. The expected weakly seasonal phenological patterns were not observed for these forests. Flowering and leaf flush patterns of Atlantic rain forest trees were significantly seasonal, concentrated at the beginning of the wettest season, and were significantly correlated with day length and temperature. These results stress the influence that seasonal variation in day length has on ever-wet forest tree phenology. Fruiting phenologies were aseasonal in all four forests. Flowering patterns did not differ significantly among three of the four forest sites analyzed, suggesting the occurrence of a general flowering pattern for Atlantic rain forest trees.